Exploring the mechanisms of neurotoxicity caused by fuzi using network pharmacology and molecular docking - An, Junsha; Fan, Huali; Han, Mingyu; Peng, Cheng; Xie, Jie; Peng, Fu (Frontiers in Pharmacology, 2022)
Safety has always been an important issue affecting the development of traditional Chinese medicine industry, especially for toxic medicinal materials, the establishment of risk prevention and control measures for toxic herbs is of great significance to improving the use of traditional Chinese medicine in clinical. Fuzi is a kind of traditional Chinese medicine and its toxicity has become the most important obstacle of limit in clinical using. In this paper, network pharmacology and molecular docking technology were used to analyze the main toxic components of Fuzi, the key targets and the mechanism of neurotoxicity. We carried out CCK-8 and WB assays, and detected LDH release and SDH activity. It was verified that aconitine caused neurotoxicity through a variety of pathways, including MAPK signaling pathway, pathways related to Akt protein, destruction of cell membrane integrity, damage of mitochondrial function affecting energy metabolism and apoptosis. What’s more, this study confirmed that aconitine could produce neurotoxicity by promoting apoptosis of hippocampus neuron and decreasing its quantity through Nissl Staining and TUNEL assay. This paper found and confirmed multiple targets and various pathways causing neurotoxicity of Fuzi, in order to provide reference for clinical application and related research.